Environment and culture in the end of incipient stage of the Jomon Period - 西田, 巌; 83820; NISHIDA, Iwao; 83821 (名古屋大学年代測定資料研究センター, 2014)
2014-03 The Higashimyo archeological site, located at Kinryu town, Saga city, Saga prefecture, was established for about a half millennium at the time of sea-level transgression in the end of incipient stage of the Jomon Period, and shell middens associated with the site were abandoned because of sea level rise. The site is composed of residential areas, tombs, shell middens, food-storage facilities, etc. in wetlands, and a set of these archeological remains belonging to the oldest stage of Jomon period are indispensable to reconstruct life style and culture of living people there. A period of residence was only 500-600 years at around 8000 cal yr BP, as revealed by AMS 14C dating. During the period, a large-scale environmental change has affected people lived there, as estimated by archeological remains excavated. The archeological survey and analysis of excavated materials at the Higashimyo site suggests clear and firm views of the environmental change and people's life styles at the end of incipient stage of the Jomon Period in Japan. 佐賀市東名遺跡は縄文時代早期末の遺跡で、国内最古の湿地性貝塚である。また居住地・墓地・貝塚・貯蔵施設がセットで確認され、当該期の生活様式や文化を知る上で希少な資料であると同時に、日本の縄文文化を研究する上で欠くことのできない遺跡である。東名遺跡の整理調査は発掘調査以来継続中で、近年の自然科学分析、特に炭素年代測定により、自然環境を含めた遺跡の変遷が明らかになりつつある。遺跡の存続期間は500～600年間と比較的短いが、その変遷には環境変動が大きく影響し、その痕跡を遺跡から読み取ることができ、さらに、高度な縄文文化が早期段階に存在してことを裏付ける数多くの資料が出土している。東名遺跡の調査・分析により、遺跡形成を取り巻く環境変動や遺跡の変遷とともに、縄文時代早期末の実像が明らかになりつつある。 名古屋大学年代測定総合研究センターシンポジウム報告 departmental bulletin paper